(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to develop interactive media based on Google Sites using the Problem Based Learning (PBL) model that is valid, practical, and effective for learning IPAS in grade IV of elementary schools. This research is a research and development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. Product testing was carried out through validation by material experts, language experts, and media experts, followed by practicality tests by teachers and students and effectiveness tests through media application to grade IV students at SD Negeri 14 Gadut, SD Negeri 07 Kapau, and SD Negeri 01 Kapau. The results showed that the media obtained an average validity of 93.73% with a very valid category. The results of practicality showed that the responses of teachers and students were in the very practical category. Meanwhile, the effectiveness results based on the N-Gain value showed a score of 0.77 at SD Negeri 14 Gadut, 0.78 at SD Negeri 07 Kapau, and 0.75 at SD Negeri 01 Kapau, which are included in the high category. These findings indicate that interactive media based on Google Sites can improve student learning outcomes while supporting their active involvement in the problem-solving-based learning process. Thus, the developed media is declared valid, practical, and effective for use in science learning in elementary schools.